Relationship Between Knowledge and Attitude at Students Smk Swasta Arjuna Laguboti About Dagusibu (Get, Use, Save, Discard) Medicine - Sibagariang, Ayu; Tamba, Rosanto; Sirait, Wenni Elisabet (International Journal of Nursing and Midwifery Research, 2025)
People generally carry out treatment independently and go to the doctor. Dagusibu is good and correct management of medicines in the household, namely getting, using, storing and disposing of. The aim of this research is to determine the relationship between knowledge and the behavior at students SMK Swasta Arjuna about DAGUSIBU (Get, Use, Save, Dispose) of drugs. This research is a correlation research method with a cross sectional survey approach, a correlation study. The total sample was 76 respondents, sample selection was carried out using the purposive sampling method with the Spearman Rho test. The research results showed that the majority of respondents were 16 years old, 41 respondents (53.9%), 70 respondents (92.1%). The majority of students SMK Swasta Arjuna Laguboti knowledge about Dagusibu was good knowledge, namely 51 respondents (67.1%) and 23 respondents (30.3%) had sufficient knowledge. The behavior at students SMK Swasta Arjuna about the use of DAGUSIBU had positive behavior of 48 people (63.2%) and negative behavior of 28 people (38.8%). There is no relationship between knowledge and the behavior at students SMK Swasta about DAGUSIBU (Get, Use, Save, Dispose) of drugs with a p value: 0.284. In this research, it is hoped to increase knowledge and behavior about Dagusibu medicine so that students SMK Swasta Arjuna Laguboti become people who behave appropriately in Dagusibu medicine.